1996
DOI: 10.1165/ajrcmb.15.2.8703474
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of laminins and their integrin receptors in developing and adult human lung.

Abstract: Laminins (Ln) appear to play an important role in the morphogenesis of airways. We studied the expression of different laminin chains and their integrin receptors in fetal and adult lung by immunohistochemistry. Special attention was focused on the changes in the expression of these proteins during the development from the pseudoglandular (PG) and canalicular stages to adult lung, and on the possible implications of the changes for the normal lung development. The most significant changes in the expression pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
82
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 53 publications
7
82
1
Order By: Relevance
“…They form a growing protein family consisting of at least of 14 trimeric proteins and containing ␣-, ␤-, and ␥-chains; at present, five ␣-, three ␤-, and three ␥-chains have been described (11,12). Different Ln isoforms show distinct localizations in various organs, such as stomach and airways (13,14), suggesting organ-or tissue-specific functions. Immunolocalization studies have revealed a complex Ln composition in BM of many epithelial tissues.…”
Section: T He Adrenal Cortex Develops From Mesenchymal Cellsmentioning
confidence: 99%
“…They form a growing protein family consisting of at least of 14 trimeric proteins and containing ␣-, ␤-, and ␥-chains; at present, five ␣-, three ␤-, and three ␥-chains have been described (11,12). Different Ln isoforms show distinct localizations in various organs, such as stomach and airways (13,14), suggesting organ-or tissue-specific functions. Immunolocalization studies have revealed a complex Ln composition in BM of many epithelial tissues.…”
Section: T He Adrenal Cortex Develops From Mesenchymal Cellsmentioning
confidence: 99%
“…Specifically, several laminin subunits have been identified in the matrix-rich basement membrane of AECs in vivo (Coraux et al, 2002;Mizushima et al, 1998;Pierce et al, 1998;Virtanen et al, 1996). This basement membrane is covered by a sheet of cells composed mainly of type-I (AT1, alveolar type-I pneumocytes) cells (Crapo et al, 1982).…”
mentioning
confidence: 99%
“…The type-II cells produce surfactant, proliferate and differentiate into type I cells (Crapo et al, 1982;Fehrenbach, 2001;Uhal, 1997). In the basement membrane of the lung, subunits of laminin show precise, developmentally regulated patterns of expression (Coraux et al, 2002;Mizushima et al, 1998;Pierce et al, 1998;Virtanen et al, 1996). For example, laminin α1 expression is restricted to early human lung morphogenesis, whereas the laminin α5 is continuous from early lung development to adult life (Pierce et al, 1998;Virtanen et al, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the three subunits of LN5 is regulated differentially in cancer cell lines and in normal and malignant tissues including HCC [9][10][11] . Indeed, LNγ2 has been shown to be secreted as a single subunit in gastric cancer [12] .…”
Section: Introductionmentioning
confidence: 99%